Queering Criminology in Theory and Praxis 2022
DOI: 10.1332/policypress/9781529210699.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

‘PREA Is a Joke’: A Case Study of How Trans PREA Standards Are(n’t) Enforced

Abstract: In 2012 PREA (Prison Rape Elimination Act) added specific guidelines to protections already enacted to reduce prison rape. These new protections were specific to trans and intersex folx currently in prison. Although these are federal “mandatory guidelines,” the enforcement of these standards varies between facilities. Drawing from a subsample of 9 trans participants (from a broader interview study) who experienced incarceration while identifying as trans, I focus primarily on the narrative of Naomi, a Black tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Such findings are not that uncommon. Carrillo (2022), for example, surveyed over 1,100 incarcerated individuals, and found that nearly all of them perceived PREA as a "joke." Respondents further thought that PREA regulations were not being followed, thus discouraging them from taking the policy seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are not that uncommon. Carrillo (2022), for example, surveyed over 1,100 incarcerated individuals, and found that nearly all of them perceived PREA as a "joke." Respondents further thought that PREA regulations were not being followed, thus discouraging them from taking the policy seriously.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of transgender people in carceral spaces is shaped by their demeaned social status in a hypermasculine prison/jail culture in which masculinity is valorized and femininity is subordinated and disdained. It is also shaped by the social organization of prison politics, the ways in which heterosexism and homophobia manifest in prisons and jails, and the failure of corrections officials to enforce zero-tolerance policies for assault (sexual or otherwise) (Carrillo 2022, Donaldson 2001, Kunzel 2008, Stanley & Smith 2015. Undergirding these contextual features of carceral spaces, a gender binary that assumes that there are two (and only two) sex categories (i.e., male and female) and two (and only two) genders (i.e., men and women) positions transgender people as either illegible or legible in ways that leave them vulnerable to discrimination, violence, and other harms ( Jenness & Fenstermaker 2014Rodgers et al 2017).…”
Section: Observed Thatmentioning
confidence: 99%